2020
DOI: 10.1186/s12889-020-08863-7
|View full text |Cite
|
Sign up to set email alerts
|

“I can’t stand it…but I do it sometimes” parental smoking around children: practices, beliefs, and conflicts – a qualitative study

Abstract: Background Many parents continue to smoke around their children despite the widely known risks of children’s exposure to tobacco smoke. We sought to learn about parental smoking behavior around children from parents’ perspective. Methods Semi-structured interviews were conducted with 65 smoking parents or partners of smoking parents of children up to age 7, to learn about home smoking rules, behaviours performed to try to protect children, and smoking-related conflicts, from parents’ perspective. Interviews w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…To reduce household SHS exposure, not only smoke-free home rules but also campaigns and community programs for parents are urgently needed to create social norms for smoke-free environments in society as a whole. Interviews with smoking Israeli parents with children aged <7 years revealed that the parents were aware of the health risks associated with SHS, but were confused about preventative methods and whether smoke-free home rules were effective 31 . Therefore, it is necessary to explain the need for smoke-free homes or to deliver the message via a campaign 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce household SHS exposure, not only smoke-free home rules but also campaigns and community programs for parents are urgently needed to create social norms for smoke-free environments in society as a whole. Interviews with smoking Israeli parents with children aged <7 years revealed that the parents were aware of the health risks associated with SHS, but were confused about preventative methods and whether smoke-free home rules were effective 31 . Therefore, it is necessary to explain the need for smoke-free homes or to deliver the message via a campaign 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Interviews with smoking Israeli parents with children aged <7 years revealed that the parents were aware of the health risks associated with SHS, but were confused about preventative methods and whether smoke-free home rules were effective 31 . Therefore, it is necessary to explain the need for smoke-free homes or to deliver the message via a campaign 31 . A randomized controlled trial on the effectiveness of household SHS interventions by community health workers found that smoking parents or caregivers with children, adopted complete smoking bans in China after the smoking hygiene intervention 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Porch doors may often be left open in Israel’s climate, which is characterized by hot summers and mild winters. A qualitative study in Israel showed that some smoking parents described smoking on the balcony and leaving the door to the living room open [ 14 ]. Outdoor porches that are directly adjacent to the apartment may be small and completely enclosed, semi-enclosed, or open (see Supplemental Figure S4 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our qualitative study of smoking parents in Israel, we found that parents in smoking families employed various strategies with different levels of restrictiveness, ranging from never permitting smoking inside or around the home, to smoking on the outside balcony with the door open or closed, to smoking only on an indoor balcony or designated areas in the home, to smoking “in” or at a window, or to smoking only when children are not present in the home. The parents themselves were often confused about the benefits of these strategies [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%